Listening to the community: identifying obesity prevention strategies for rural preschool-aged children - Pope, Katherine Jochim; Lightfoot, Alexandra F.; Harrison, Lisa Macon; Getz, Deborah; Gittelsohn, Joel; Ward, Dianne; Hannon, Tamara S.; Erinosho, Temitope (Frontiers in Public Health, 2024)
Multi-level interventions promoting healthy weight in rural preschool children aged 2-5 years are limited. With the goal of developing a community-informed obesity prevention intervention for rural preschool-aged children, the purpose of this descriptive study was to identify: 1) community settings and intervention strategies to prioritize for an intervention; 2) potential implementation challenges and solutions; and 3) immediate interventions the study team and community partners could collaboratively implement. Workshops occurred in two rural communities in Indiana (2 workshops) and North Carolina (2 workshops), with high obesity rates. A guide was developed to moderate discussions and participants voted to rank community settings and intervention strategies. There were 9-15 participants per workshop, including parents, childcare providers, and representatives of community organizations. Community settings identified as priorities for child obesity prevention included the home, educational settings (preschools), food outlets, recreational facilities, and social media. Priority intervention strategies included providing nutrition and physical activity education, increasing access to healthy foods and physical activity in the built environment, and enhancing food security. Potential intervention implementation challenges centered on poor parental engagement; using personalized invitations and providing transportation support to families were proffered solutions. Immediate interventions to collaboratively implement focused on making playgrounds aesthetically pleasing for physical activity using game stencils, and nutrition education for families via quarterly newsletters. This participatory approach with community partners provided insight into two rural communities' needs for child obesity prevention, community assets (settings) to leverage, and potential intervention strategies to prioritize. Findings will guide the development of a multilevel community-based intervention.